Andanças e paranças pelos sertões da área de irradiaçao paulista (1500-1899) - Maria Luiza Andreazza (Caravelle)
This text aims to recreate the historicity of the movements and the installation of the inhabitants of the village of São Vicente and of the paulistas in southern American portuguese territories. At the beginning, the effects of the New World upon Europeans are tackled, as well as the Portuguese’s colonizing measures to protect their lands. Afterwards, this text tries to present the different institutional forms taken by the harbour offices in the present state of São Paulo, as well as the characteristics of paulista’s social forming, the caipira’s culture specific location.